Physical layer security in visible light communication systems with randomly located colluding eavesdroppers - Cho, S; Chen, G; Coon, J (IEEE, 2018)
This letter investigates the secrecy performance in visible light communication (VLC) in the presence of randomly located colluding eavesdroppers (EDs). Colluding EDs can combine their observations and degrade the secrecy performance of the VLC systems. Utilizing the numerical inversion of a characteristic function, the probability distribution of the combined signal-to-noise ratio of colluding EDs is analyzed. The closed-form expression of the secrecy outage probability is derived and verified by Monte Carlo simulations.